THE PERISHED MADHHABS AND THEIR IMAMS IN HISTORICAL REVIEW - Meirison Meirison; Yelmi Eri Firdaus; Makhsus Makhsus (Jurnal Al-Ahkam: Jurnal Hukum Pidana Islam, 2021)
This article aims to analyze the role of madhab scholars and their students and the state in perpetuating their schools. Every nation on earth has scholars in various fields of religion and the world. They respect and appreciate these nations for their role in building their society religiously, intellectually, and culturally. These scholars created Islamic civilization in Baghdad, Cairo, Kairouan, Damascus, and Andalus, etc. That civilization taught the world at a time of European ignorance of the Ages by conducting a qualitative descriptive analysis literature study. We found that some scholars did not influence their knowledge for various reasons, including the cleric Imam Al-Layth bin Saad, Tabari, and at-Thaur they are part of famous jurists of his time. This study discusses the doctrine of Al-Awza'i during the Umayyad period (138–206 AA/756–821 AD). It was the central doctrine of the first three Umayyad princes, Abdulrahman, Hesham, and A.L.-Hakam. This study also discusses the life of Al-Awza'i and his spread in Al-Andalus and the contribution of the people of Sham in transferring the doctrine to Al-Andalus because it became the primary doctrine of the Umayyad Emirate. in the era of Abdulrahman Bin Mo'awyeh. In addition, the eminent scholars and Awza'i judges, the reasons behind this decline and doctrine from Al-Andalus were also discovered. Keywords: Doctrines, hidden jurisprudence, historical, Islam